Analisis Pengaruh Return On Assets (ROA), Earning Per Share (EPS), Debt to Equity Ratio (DER) Terhadap Price to Book Value (PBV) Pada Perusahaan Manufaktur ( Studi kasus Perusahaan Food and Beverages yang terdaftar di BEI Tahun 2010-2013 ) - Wulandari, Cici, Drs. Syamsudin, M.M (2015)
PBV is the ratio betwen stock market price and book value per share. PBV showed how far ability of firm create a relative value of the firm toward the capital invested. The higher the ratio of PBV, more successful the firm are creating a value for shareholders. This research have as a purpose to examine influence factors of return on assets (ROA), earning per share (EPS), debt to equity ratio (DER) to price to book value (PBV). The research was conducted using purposive sampling for sampling is used and there are 14 companies that visited during the study. Analytical techniques used in the study is multiple regression analysis by using SPSS where previously the data was tested using the classical assumptions. The result showed that return on assets (ROA), earning per share (EPS), debt to equity ratio (DER) jointly effect to price to book value (PBV) with values of adjusted R² is 42,5%. Individually while return on assets (ROA) and earning per share (EPS) have positive relating and significant with price to book value (PBV), while debt to equity ratio (DER) have negative relating and not significant effect to price to book value (PBV).